A self-powered photodetector using a pulsed triboelectric nanogenerator for actual working environments with random mechanical stimuli. (December 2021) - Wang, Tingyu; Gu, Guangqin; Shang, Wanyu; Gan, Jiahui; Zhang, Wenhe; Luo, Hongchun; Zhang, Bao; Cui, Peng; Guo, Junmeng; Yang, Feng; Cheng, Gang; Du, Zuliang
Abstract: The self-powered sensing systems based on impedance matching effect have been proposed by using a triboelectric nanogenerator (TENG) as power source, which have attracted widespread attention in the field of Internet of Things. However, the output voltage and current of the conventional TENG are affected by not only the load impedance but also the working frequency of TENG, leading to inaccurate sensing results in actual working environments with random mechanical stimuli. For solving this problem, a self-powered sensing system using a Pulsed-TENG with a synchronous trigger switch has been proposed here, in which the output voltage and current of Pulsed-TENG are independent on its working frequency. The measured performances of a self-powered photodetector have verified that same detection results could be obtained for various rotation frequencies of a rotating Pulsed-TENG. Two self-powered detection modes, current mode and voltage mode, have been developed. In the current detection mode, the output current increased linearly with light intensity, and the detectable range of light intensity is 0–1 W/m 2 . In the voltage detection mode, the output voltage is inversely proportional to the light intensity, and the detectable range of light intensity is 9–403 W/m 2 . Finally, a self-powered photodetection system with visual display function has been developed, in which the light intensity can be displayed intuitively by the number of lighted LEDs. Since the output voltage and current of Pulsed-TENG are independent on its working frequency, the self-powered sensing system based on Pulsed-TENG proposed here has provided a promising strategy suitable for the actual working environments with random mechanical stimuli. Graphical Abstract: A self-powered photodetector using a Pulsed-TENG with a synchronous trigger switch has been proposed. The same detection results could be obtained for various rotation frequencies of a rotating Pulsed-TENG. ga1 Highlights: A self-powered photodetection system based on Pulsed-TENG is developed. The output voltage of Pulsed-TENG and the photodetection results are not affected by the frequency of mechanical stimuli. Based on the output characteristic of Pulsed-TENG, both current and voltage modes are developed. Based on the voltage mode, a self-powered photodetection system with visual display function is developed.